Integrative treatment program for the treatment of children with autism spectrum disorder: A prospective observational case series - Lee, Boram; Park, Serin; Kwon, Hyun Jeong; Hwang, Gwi Seo; Kim, Moonju (Frontiers in Neurology, 2023)
Background In a situation where conventional treatments for autism spectrum disorder (ASD) are labor-intensive and there are concerns about the side effects of conventional medications, a 6-month integrative treatment program, including herbal medicine (HM), Floortime, and sensory enrichment therapy (SET) has been used on children with ASD in Korean medicine clinical settings. Methods We observed the treatment responses of 18 children with ASD (66.7% male, mean age 3.9 ± 0.9 years) to the integrative treatment program as part of a prospective, single-center, observational case series. Individualized HMs were administered according to the patient's symptoms, and parents were instructed to perform Floortime and SET with their children at home for 2 h and 20 min a day, 5 days a week, respectively. The Childhood Autism Rating Scale (CARS) and Autism Behavior Checklist (ABC) were used to evaluate the core symptoms of ASD. A linear mixed model for repeated measures was used for analyzing the effect of the program over time, and logistic regression used to explore the predictors of treatment response. Results The CARS and ABC scores were significantly improved from 34.58 ± 6.27 and 69.28 ± 15.73 at baseline to 28.56 ± 6.05 and 39.67 ± 20.36 after 6 months (p < 0.0001, respectively). No serious adverse events (AEs) were reported, and compliance with HM, Floortime, and SET was high at >90%. Conclusion This 6-month integrative treatment program appears to be a potentially effective, safe, and feasible option for children with ASD. Low baseline CARS scores may be predictors of higher treatment response.